Seismic Attributes Analysis of Fluvial Channel in Angsi Field, Malay Basin - Baharudin, Siti Nur Amiha (2016)
This project focuses on the improvement of attributes analysis by incorporating seismic interpretation of channel geometries for Group I in Angsi field, Malay Basin. Seismic attribute is a tool that helps us visually enhance or quantify features of interest area in a seismic dataset. The interpretation of attributes from time slices have enabled detailed structural and sedimentological features to be recognized and characterized. The study area composed of fluvial channel geomorphology which recognized as good reservoir with presence of channels. The attributes map will reveal detail features of the fluvial channel later that can be considered as potential points of hydrocarbon accumulation. The variability in fluvial channel type and geometry is controlled by various factors including base-level, climate, tectonic, sediment types, and hydrology. In order to improve channel interpretation in seismic, various attributes such as RMS amplitude and variance were used. All the interpretation and analysis were conducted by using PETREL 2013. The application of seismic attributes is important and widely used in further exploration and production of oil and gas.